2013
DOI: 10.3109/0284186x.2013.819995
|View full text |Cite
|
Sign up to set email alerts
|

Changes in non-surgical management of stage III non-small cell lung cancer at a single institution between 2003 and 2010

Abstract: (2014) Changes in nonsurgical management of stage III non-small cell lung cancer at a single institution between 2003 and 2010, Acta Oncologica, 53:3, 316-323,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The 46% of our cohort with a stage IIIA NSCLC had a median OS of 10.4 months, which is comparable to that of our patients with stage III NSCLC who were undergoing conventional RT (median OS 11.0 months). 19 Experience with SABR for ultracentral tumors is limited. One study reported significantly higher treatment-related mortality for tumors abutting the trachea, main bronchi, or lobar bronchi (22%) versus for moderately central lesions (0%) after treatment with five fractions of 9 or 10 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…The 46% of our cohort with a stage IIIA NSCLC had a median OS of 10.4 months, which is comparable to that of our patients with stage III NSCLC who were undergoing conventional RT (median OS 11.0 months). 19 Experience with SABR for ultracentral tumors is limited. One study reported significantly higher treatment-related mortality for tumors abutting the trachea, main bronchi, or lobar bronchi (22%) versus for moderately central lesions (0%) after treatment with five fractions of 9 or 10 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to similar patients treated between 2003 and 2010 at our institute, the results of the present study show comparable OS values in the sCRT group (17 and 17.4 months). However, in the cCRT group, the OS values were considerably higher than those reported earlier (29 vs. 18.6 months) [28]. The difference might be as a result of several factors, including patient selection; new treatments, such as the use of targeted therapy on progression; more aggressive treatment of (oligo) metastatic disease; standard use of IMRT/VMAT with consistently better lung/OAR sparing [12,13]; or improved dosimetry and daily image guidance.…”
Section: Discussionmentioning
confidence: 63%
“…We estimate that about 50 patients per year undergo definitive concurrent or sequential CRT for stage III NSCLC [3], which suggest that about 2.5% of patients (9 of 350) have undergone surgical intervention for serious structural complications. This indicates that the estimated incidence of operation for complications after high-dose CRT is likely to be low.…”
Section: Commentmentioning
confidence: 99%
“…Despite the risks accompanying the operation, several patients achieved a prolonged survival. To put the median overall survival of 19 months from diagnosis of the CRT complication and 11 months after operation into some kind of context, we have previously reported a median overall survival after the start of radiotherapy for locally advanced NSCLC treated with CRT of 18.6 months [3] and a median overall survival of 75.9 months after a median follow-up of 80.4 months (with 5.5% 90-day mortality rate) after up-front trimodality therapy for non-Pancoast NSCLC [6]. Any comparisons with a salvage operation for recurrent or persistent tumor after CRT are limited by our median follow-up in this cohort of 12.1 months with a 90-day mortality rate of 6.7% [7].…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation